Quining Ecofeminism: Saintifikasi Keadilan Iklim dan Gender: Quining Ecofeminism: The Saintification of Climate Justice and Gender - Rahima, Raisa (Jurnal Filsafat Indonesia, 2024)
Ecofeminism as a theory is far from complete to solve the problems of climate injustice, gender and even other problems that may be under the umbrella of ecofeminism. This article finds that ecofeminism is sufficient as a scientific stance (axiology), but not enough at the epistemic level. The tendency of ecofeminism theorists to characterize the ontology of nature and women: with specific gender or other analogies, instead of focusing on the scope of "explanation and methodology" makes it not holistic and stuck as an academic study. The rest of this article constructs an adequate epistemology for academics to use ecofeminism, namely with W. V. O. Quine's naturalized epistemology as an offer to lubricate the ontological burden of ecofeminist theory which actually makes the ecofeminist journey towards climate and gender justice stuck.